THE INFLUENCE OF THE INFLUENCE OF PRODUCTS, PRICE PERCEPTIONS, PROMOTIONS ON THE PURCHASE DECISIONS OF THE 6TH CLASS ELEMENTARY BOOKS IN PT. YUDHISTIRA GHALIA INDONESIA.: abstract - ari dwi astono; Dwi Kuswanto (Sekolah tinggi ilmu ekonomi pemuda, 2022)
This study aims to determine the effect of product, price perception, promotion of purchasing decisions in the 6 th grade tematik book at PT Yudhistira Ghalia Indonesia. The data used in this study are primary data which is done by distributing questionnaires. The method used to take samples in this study is the census method with a total sample of 100 respondents or a grade 6 SD teacher. Data analysis techniques used are validity test, reliability test, multicollinearity test, heterocedasticity test, linearity test, multiple linear regression analysis test. The analytical method used in this study is multiple linear regression analysis using the SPSS version 16. The results obtained in the form of product related to purchasing decisions in the 6 th grade tematik book at PT Yudhistira Ghalia Indonesia. While price perception dan promotion is significant and positive for purchasing decisions in the 6 th grade tematik book at PT Yudhistira Ghalia Indonesia.